LAB KIT DEVELOPMENT TO IMPROVE STUDENT’S ATTITUDES AND ACHIEVEMENTS IN DISTANCE LEARNING - Adhitya Chandra Permana (Universitas Bhinneka PGRI, 2022)
A shortcoming of distance learning is the lack of substantive integration of hands-on activities into online classrooms. We conducted a research and development study, where the lab kits and tutorial videos were sent to students to perform experiments in their own homes. We planned, tested, developed, improved, and implemented kits into experimental distance learning. This research was conducted to improve previous studies in linear subjects. Findings have implications for distance learning in rural areas that have limitations. Furthermore, our findings illustrate the potential amplifying effect of this learning environment configuration for science teachers. Thirty-two students, four experts, and three science teachers participated in this research. The product’ validity and feasibility were obtained by descriptive analysis of experts and students' assessment data. Students’ learning motivation and activities were observed and analyzed descriptively. Students’ cognitive learning outcomes were obtained by analyzing pretest and posttest data using paired sample t-test. This learning helped students achieve intellectual goals by significantly improving students’ learning motivation, activities, and cognitive outcomes.